Neuro-cognitive Underpinning of Co-morbidity between Developmental Dyslexia and Attention-Deficit Hyperactivity Disorder (ADHD) - Larysa Zasiekina (Психолінгвістика)
Developmental Dyslexia is a specific reading and writing disability despite of normal intelligence, educational instruction and socio-cultural opportunity. Attention-deficit hyperactivity disorder (ADHD) is a condition that affects millions of children and often persists into adulthood. ADHD can include a combination of problems, such as difficulty sustaining attention, hyperactivity and impulsive behaviour. The frequent co-morbidity of dyslexia and ADHD posed the question of the issue whether common causal mechanism can be identified. There are several causal explanation of the co-morbidity between dyslexia and ADHD. Firstly, the symptoms of ADHD associated with dyslexia are a secondary consequence of reading problems (‘phenocopy’ hypothesis). However, the finding could not substantiate in later studies. Therefore, the first aim the present research is to identify the frequency and nature of co-morbidity between dyslexics and ADHD children.